A Novel Association between YKL-40, a Marker of Structural Lung Disease, and Short Telomere Length in 10-Year-Old Children with Bronchopulmonary Dysplasia - Ewa Henckel; Anna James; Jon R Konradsen; Björn Nordlund; Malin Kjellberg; Eva Berggren-Broström; Gunilla Hedlin; Sofie Degerman; Kajsa Bohlin (MDPI AG, 2021)
Extremely preterm infants are born with immature lungs and are exposed to an inflammatory environment as a result of oxidative stress. This may lead to airway remodeling, cellular aging and the development of bronchopulmonary dysplasia (BPD). Reliable markers that predict the long-term consequences of BPD in infancy are still lacking. We analyzed two biomarkers of cellular aging and lung function, telomere length and YKL-40, respectively, at 10 years of age in children born preterm with a history of BPD (n = 29). For comparison, these markers were also evaluated in sex-and-age-matched children born at term with childhood asthma (n = 28). Relative telomere length (RTL) was measured in whole blood with qPCR and serum YKL-40 with ELISA, and both were studied in relation to gas exchange and the regional ventilation/perfusion ratio using three-dimensional V/Q-scintigraphy (single photon emission computer tomography, SPECT) in children with BPD. Higher levels of YKL-40 were associated with shorter leukocyte RTL (Pearson's correlation: −0.55, p = 0.002), but were not associated with a lower degree of matching between ventilation and perfusion within the lung. Serum YKL-40 levels were significantly higher in children with BPD compared to children with asthma (17.7 vs. 13.2 ng/mL, p < 0.01). High levels of YKL-40 and short RTLs were associated to the need for ventilatory support more than 1 month in the neonatal period (p < 0.01). The link between enhanced telomere shortening in childhood and structural remodeling of the lung, as observed in children with former BPD but not in children with asthma at the age of 10 years, suggests altered lung development related to prematurity and early life inflammatory exposure. In conclusion, relative telomere length and YKL-40 may serve as biomarkers of altered lung development as a result of early-life inflammation in children with a history of prematurity.